2017
DOI: 10.1007/s00264-017-3650-8
|View full text |Cite
|
Sign up to set email alerts
|

Inefficacy of autologous bone marrow concentrate in stage three osteonecrosis: a randomized controlled double-blind trial

Abstract: Purpose The fracture stage of non-traumatic osteonecrosis (ON stage 3) of the femoral head (ONFH) has an unfavourable prognosis frequently requiring total hip replacement (THR). The percentage could be lowered after core decompression. In earlier non-fracture ON stages, implantation of autologous bone marrow aspirate concentrate (BMAC) improved the effect of core decompression. The purpose was to evaluate the effect of BMAC in addition to core decompression in stage 3 ONFH. Methods A double blind RCT was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 20 publications
(26 reference statements)
2
133
0
1
Order By: Relevance
“…The authors [37,[40][41][42][43][44] of this issue critically address specific problems-namely cell quality and competence, and microenvironmental changes occurring at the bone osteonecrosis level. BMSC-which are supposed to be Bfunctionally competent^-are often being collected from the BM of patients with bone disease and concomitant risk factors for bone marrow disease (corticosteroids, alcohol abuse…).…”
Section: Cell Therapy and Osteonecrosismentioning
confidence: 99%
“…The authors [37,[40][41][42][43][44] of this issue critically address specific problems-namely cell quality and competence, and microenvironmental changes occurring at the bone osteonecrosis level. BMSC-which are supposed to be Bfunctionally competent^-are often being collected from the BM of patients with bone disease and concomitant risk factors for bone marrow disease (corticosteroids, alcohol abuse…).…”
Section: Cell Therapy and Osteonecrosismentioning
confidence: 99%
“…This study compared 2 groups: core decompression plus saline injection compared with core decompression plus BMAC implantation. No differences were found in total hip replacement requirements, clinical symptoms, or radiologic results through 2‐year follow‐up [108]. However, a level II study by Pilge et al [109] showed that the BMAC group had a decreased need for hip arthroplasty.…”
Section: Common Regenerative Methodsmentioning
confidence: 95%
“…The only level I study using BMAC reported at the time of this review [108] treated patients with stage 3 osteonecrosis of the femoral head. This study compared 2 groups: core decompression plus saline injection compared with core decompression plus BMAC implantation.…”
Section: Common Regenerative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is encouraging and I would like to congratulate authors for their study, theoretically, procedures that provide a blood supply for necrotic area could be more effective than conventional CD or even structural allografts. Conversion to total hip arthroplasty (THA) and any progress or changes in staging were considered as outcome measurement in this study which are used repeatedly in same studies [3][4][5]. The authors reported success rate of 87.5% because at final followup, only three out of 24 hips have been converted to THA; I do not agree with this result.…”
mentioning
confidence: 99%